Історія медицини : методичні рекомендації для студентів I курсу медичного факультету [Електронний ресурс] - Проценко, Олена Сергіївна; Кириченко, Максим Іванович; Protsenko, Olena; Kyrychenko, Maksym (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Методичні рекомендації містять основні рекомендації щодо підготовки студентів I курсу медичного факультету до занять, заліку із дисципліни за вибором студента «Історія медицини» і призначені здобувачам вищої медичної освіти у вищих медичних навчальних закладах освіти України ІІІ-ІV рівнів акредитації: спеціальність «222 Медицина», галузь знань «22 Охорона здоров’я», кваліфікація «Лікар».

The methodological guidance contain the main recommendations for preparing first-year medical students for classes, tests in the discipline of the student's choice ‘History of Medicine’ and are intended for applicants for higher medical education in higher medical educational institutions of Ukraine of III-IV accreditation levels: specialty ‘222 Medicine’, field of knowledge ‘22 Healthcare’, qualification ‘Doctor’.
History of medicine : methodical guidance for the first year students of the School of Medicine [Electronic resource]
The methodological guidance contain the main recommendations for preparing first-year medical students for classes, tests in the discipline of the student's choice ‘History of Medicine’ and are intended for applicants for higher medical education in higher medical educational institutions of Ukraine of III-IV accreditation levels: specialty ‘222 Medicine’, field of knowledge ‘22 Healthcare’, qualification ‘Doctor’.
Keywords: SOCIAL SCIENCES::Social sciences::Education::Subject didactics; HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; історія; історія медицини; медицина; history; history of medicine; medicine